Pengaruh Kemampuan Kerja dan Pelatihan Soft Skill Terhadap Kesiapan Kerja Fresh Graduate di Era Digital: Studi Kasus pada Mahasiswa Universitas Wijaya Kusuma Surabaya - M. Fauzil Adhim; Adrianto Trimarjono (MES Management Journal, 2025)
The purpose of this research is to examine how programming in soft skills and employability has affected the digital native job preparedness of recent college grads. College grads need to be prepared to work hard and have strong academic skills to succeed in today's technologically advanced and rapidly evolving job market. This research survey-based study employed a quantitative technique. Researchers used a purposive selection method to choose 100 students from Wijaya Kusuma University Surabaya to serve as the study's target group. For this study, we used SPSS to administer a Likert-scale questionnaire and then evaluated the results using multiple linear regression. Results demonstrated that employability significantly and positively impacted the job preparedness of recent graduates. Additionally, there was a favorable and statistically significant impact of soft skills training on fresh graduates' marketability to potential employers.